Molecular biology of oral cavity squamous cell carcinoma. (March 2020) - Hsu, Phillip J.; Yan, Kenneth; Shi, Hailing; Izumchenko, Evgeny; Agrawal, Nishant
Highlights: We review the current understanding of molecular pathways prominent in OCSCC. Treatment must be guided by patient-specific aberrations that underlie the disease. Recent advances in high-throughput sequencing technologies show great potential. New techniques detecting early genomic and epigenetic changes may improve diagnosis. Abstract: Oral cavity squamous cell carcinoma (OCSCC) is a heterogeneous and complex disease that arises due to dysfunction of multiple molecular signaling pathways. Recent advances in high-throughput genetic sequencing technologies coupled with innovative analytical techniques have begun to characterize the molecular determinants driving OCSCC. An understanding of the key molecular signaling networks underlying the initiation and progression of is essential for informing treatment of the disease. In this chapter, we discuss recent findings of key genes altered in OCSCC and potential treatments targeting these genes.